Impact of Green University on Student Environmental Behaviour in SBM ITB - Yohanes Aldiyasa Setyo Bimantoro; Achmad Ghazali (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
This study investigated the real-world impact of green university initiatives (GUIs) on students' Pro-Environmental Behaviour (PEB) at SBM ITB, while also examining environmental attitude (EA) and knowledge (EK) as possible mediating variables. A quantitative survey of 144 students, analysed using PLS-SEM, showed that GUIs had a significant effect on EA, which then positively predicted PEB. EA has also been found to significantly mediate the relationship between GUI and PEB. However, GUIs did not significantly affect EK, and the EK influence on PEB was insignificant from the analysis. Findings from this research suggest that GUIs primarily drive sustainable behaviour by supporting positive environmental attitudes rather than increasing knowledge. These findings urge higher education institution to prioritise attitudinal development in green campus programmes.